We start with the expression
\[
\frac{\sqrt[3]{27 x^{4} y^{2}}}{5 x^{\frac{1}{3}} y}
\]
First, we simplify the numerator:
\[
\sqrt[3]{27 x^{4} y^{2}} = \sqrt[3]{27} \cdot \sqrt[3]{x^{4}} \cdot \sqrt[3]{y^{2}} = 3 \cdot x^{\frac{4}{3}} \cdot y^{\frac{2}{3}}
\]
Thus, the expression becomes:
\[
\frac{3 x^{\frac{4}{3}} y^{\frac{2}{3}}}{5 x^{\frac{1}{3}} y}
\]
Next, we rewrite the denominator:
\[
5 x^{\frac{1}{3}} y = 5 x^{\frac{1}{3}} y^{1}
\]
Now we can combine the expressions:
\[
\frac{3 x^{\frac{4}{3}} y^{\frac{2}{3}}}{5 x^{\frac{1}{3}} y^{1}} = \frac{3}{5} \cdot \frac{x^{\frac{4}{3}}}{x^{\frac{1}{3}}} \cdot \frac{y^{\frac{2}{3}}}{y^{1}}
\]
Using the property of exponents \( \frac{a^m}{a^n} = a^{m-n} \), we simplify:
\[
\frac{x^{\frac{4}{3}}}{x^{\frac{1}{3}}} = x^{\frac{4}{3} - \frac{1}{3}} = x^{\frac{3}{3}} = x^{1}
\]
And for \( y \):
\[
\frac{y^{\frac{2}{3}}}{y^{1}} = y^{\frac{2}{3} - 1} = y^{\frac{2}{3} - \frac{3}{3}} = y^{-\frac{1}{3}}
\]
Putting it all together, we have:
\[
\frac{3}{5} x^{1} y^{-\frac{1}{3}} = \frac{3}{5} x^{1} \cdot \frac{1}{y^{\frac{1}{3}}}
\]
In the form \( a x^{b} y^{c} \), we identify:
- \( a = \frac{3}{5} \)
- \( b = 1 \)
- \( c = -\frac{1}{3} \)
Finally, we calculate the product of \( a, b, \) and \( c \):
\[
a \cdot b \cdot c = \frac{3}{5} \cdot 1 \cdot \left(-\frac{1}{3}\right) = -\frac{3}{15} = -\frac{1}{5}
\]